Pengaruh Profitabilitas Terhadap Nilai Perusahaan (Studi Kasus Pada Pt Total Bangun Persada Tbk Periode 2013-2022) - Rahman, Fakung (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2024)
This study aims to determine the effect of Return On Assets, Return On Equity and Net Profit Margin variables on Price to Book Value of PT Total Bangun Persada Tbk for the period 2013-2022. The research method used in this research is descriptive quantitative. Data analysis used: Descriptive Statistical Test, Normality, Multicollinearity, Heteroscedasticity, Autocorrelation, Multiple Linear Regression, t Test (Partial), F Test (Simultaneous), and Coefficient of Determination (R2). The research results from the t test show that partially both Return On Assets, Return On Equity and Net Profit Margin have no effect on Price to Book Value. Likewise with the results of the F test (simultaneously), the three independent variables ROA, ROE and NPM have no effect on PBV. And from the test results of the coefficient of determination (R2), the adjusted R square value is 0.361, which means that the influence of ROA, ROE and NPM variables on PBV in this study is only 36.1%, while the remaining 63.9% is influenced by other variables not examined in this study.